Physical and oxidative stability of emulsions treated with bitter almond gum–soy protein isolate Maillard conjugates. (December 2021) - Ghaedi, Negar; Hosseini, Ebrahim
Abstract: The conjugation with carbohydrates potentially improves the functional properties of proteins. This study aimed to investigate the physical and oxidative stability of oil-in-water emulsions stabilized by bitter almond gum-soy protein isolate (BAG-SPI) conjugates (1:1, 1:3, 3:1). The dry-heated Maillard conjugation significantly improved water holding capacity and solubility of SPI proportion with BAG ratio in the conjugate ( p  < 0.05). The conjugation with BAG changed the particle size and zeta potential of SPI remarkably. This process changed the rheological behavior of SPI from Newtonian toward shear-thinning, except for BAG-SPI (1:3) conjugate, which behaved like SPI. The emulsion prepared with BAG-SPI (3:1) conjugate exhibited the highest physical stability due to its potential to produce smaller oil droplets and higher viscosity. However, the conjugation process declined oxidative stability. Therefore, a combination of SPI and glycated SPI with a higher BAG ratio may be suitable for stabilizing the emulsions for a long time. Graphical abstract: Image 1 Highlights: Maillard conjugation improved functional properties of soy protein isolate (SPI). Bitter almond gum (BAG) changed the structure and rheological properties of SPI. SPI and BAG retarded oil oxidation in the o/w emulsions stronger than conjugates. Glycated SPI with a higher BAG ratio physically stabilized the emulsion.